2022
DOI: 10.1111/vox.13383
|View full text |Cite
|
Sign up to set email alerts
|

Dose‐dependent effects of red blood cell transfusion and case mix index on venous thromboembolic events in spine surgery

Abstract: Background and Objectives: Venous thromboembolic (VTE) events represent a major source of morbidity and mortality in spine surgery. Our goal was to assess whether a dose-response relationship exists between red blood cell (RBC) transfusion and postoperative VTE events among spine surgery patients.Materials and Methods: A total of 786 spine surgery patients at a single institution who received at least 1 RBC unit perioperatively were included (2016)(2017)(2018)(2019).Patients were stratified based on RBC transf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 27 publications
(36 reference statements)
0
8
0
Order By: Relevance
“…Adult spinal deformities are a range of heterogeneous abnormalities including scoliosis, kyphosis, lordosis and spondylolisthesis, all of which can lead to imbalances in the structural support of the spine 24 25. Despite significant advances in surgical techniques and equipment, spinal deformity surgery is still one of the most invasive surgical procedures that may cause significant blood loss and postoperative anaemia,26–28 which brings the requirement for blood transfusions and the increase the associated risks including infections, thromboembolic events, extended hospital stay and may even affect prognosis 29–31. However, currently, there is no standard perioperative treatment for postoperative anaemia in this group of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Adult spinal deformities are a range of heterogeneous abnormalities including scoliosis, kyphosis, lordosis and spondylolisthesis, all of which can lead to imbalances in the structural support of the spine 24 25. Despite significant advances in surgical techniques and equipment, spinal deformity surgery is still one of the most invasive surgical procedures that may cause significant blood loss and postoperative anaemia,26–28 which brings the requirement for blood transfusions and the increase the associated risks including infections, thromboembolic events, extended hospital stay and may even affect prognosis 29–31. However, currently, there is no standard perioperative treatment for postoperative anaemia in this group of patients.…”
Section: Discussionmentioning
confidence: 99%
“…14,18 Our study aligns with the findings of previous studies on only RBC transfusions compared to those not transfused which found RBC transfusions increase risk of thromboembolic events. [6][7][8]12 The biological pathways for red cells predisposing to thrombosis have been elucidated. 19 Quantitative and qualitative red cell pathologies may contribute to arterial and venous thrombosis.…”
Section: Discussionmentioning
confidence: 99%
“…There is a substantial body of knowledge from previous studies demonstrating that perioperative red blood cell (RBC) transfusions increase postoperative VTE across several surgery types, suggesting patients receiving transfusions deserve special attention and treatment when considering VTE risk. [4][5][6][7][8] It has been proposed that RBC changes during long-term storage such as increased aggregability and decreased cell membrane deformability are responsible for the increased risk of VTE following transfusion. 9 In platelets, storage-induced activation, alterations in adenosine triphosphate and nitric oxide may lead to defects in platelet aggregation.…”
mentioning
confidence: 99%
“…[ 1 2 3 4 5 6 ] They are associated with longer hospital stays, decreased satisfaction, and worse outcomes. [ 2 3 4 5 6 7 8 9 10 11 12 ] While undergoing spine surgery is, itself, a risk factor for developing VTE, many factors are patient specific. [ 2 3 4 5 6 7 8 9 10 11 12 ] Despite prevalent literature on the issue, predictive capabilities remain limited.…”
Section: Introductionmentioning
confidence: 99%
“…[ 2 3 4 5 6 7 8 9 10 11 12 ] While undergoing spine surgery is, itself, a risk factor for developing VTE, many factors are patient specific. [ 2 3 4 5 6 7 8 9 10 11 12 ] Despite prevalent literature on the issue, predictive capabilities remain limited. [ 13 ] In the age of big data and machine learning, it is now possible to extract previously unnoticed trends from large datasets.…”
Section: Introductionmentioning
confidence: 99%